Effect of Annealing Temperature on Film Morphology of Organic–Inorganic Hybrid Pervoskite Solid‐State Solar Cells. (13th February 2014) - Dualeh, Amalie; Tétreault, Nicolas; Moehl, Thomas; Gao, Peng; Nazeeruddin, Mohammad Khaja; Grätzel, Michael
<x xml:space="preserve">Abstract</x> Organic–inorganic hybrid perovskites have attracted attention as successful light harvesting materials for mesoscopic solid‐state solar cells and led to record breaking efficiencies. The photovoltaic performance of these devices is greatly dependent on the film morphology, which in turn is dependent on the deposition techniques and subsequent treatments employed. In this work the perovskite film is deposited by spin‐coating a precursor solution of PbCl2 and CH3NH3I (1 to 3 molar ratio) in dimethylformamide. Here, the role of the temperature used in the annealing process required to convert the as deposited solution into the perovskite material is investigated. It is found that the conversion requires sufficiently high temperatures to ensure the vaporization of solvent and the crystallization of the perovskite material. However, increasing the annealing temperature too high leads to the additional formation of PbI2, which is detrimental to the photovoltaic performance. Furthermore, the effect of the annealing temperature on the film formation, morphology, and composition is examined and correlated with the photovoltaic performance and device working mechanisms.